Anemia in children from 6 to 36 months in a urban Health Center. Huánuco, 2016 - Cóndor-Cisneros, Julio (2019)
In order to determine whether the failure to exclusively breastfeed, inadequate supplementation with multimicronutrients and acute diarrheal disease are related to anemia in children from 6 to 36 months, attended at the Pillco Marca Class health center, during 2016 . A quantitative approach study was carried out, with independent, analytical, observational and retrospective cases and controls design in 86 clinical histories of children from 6 to 36 months of age, 43 clinical histories for both cases and controls. It was evidenced that non-exclusive breastfeeding p = 0.0002, inadequate multimicronutrient supplementation p = 0.000, and the presence of acute diarrheal disease p = 0.000, were related to the presence of anemia in children from 6 to 36 months old. It is concluded that there is an important association between non-compliance with exclusive breastfeeding, inadequate supplementation with multimicronutrients, and the presence of acute diarrheal disease, as risk factors associated with the development of anemia in the children under study. On the other hand, the significant association between sociodemographic characteristics was not found: sex, age and socioeconomic status of the mother; as risk factors associated with the development of anemia.